2021
DOI: 10.1038/s41598-021-86445-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of female lifestyle factors and risk of recurrent pregnancy loss

Abstract: It is known that lifestyle factors affect sporadic miscarriage, but the extent of this on RPL (recurrent pregnancy loss) is less well known. A systematic review and meta-analysis was performed to assess the associations between lifestyle factors and RPL. Studies that analysed RPL in the context of BMI, smoking, alcohol and caffeine intake were included. The primary and secondary outcomes were odds of having RPL in the general population and odds of further miscarriage, respectively. Underweight and women with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 44 publications
1
41
2
3
Order By: Relevance
“…It was found that for every 100 mg/day increment of caffeine consumption, the risk of SAB was increased by 8% (RR = 1.08; 95% CI: 1.04-1.13) and stillbirth by 9% (RR = 1.09; 95% CI: 1.02-1.16). In a meta-analysis of 2 studies by Ng et al [47] it was shown that the risk of recurrent pregnancy loss in the group of women with higher caffeine consumption (> 99 mg/day) compared to the group with lower caffeine consumption (< 99 mg/day) was higher, but not statistically significant (OR = 1.35; 95% CI: 0.83-2. 19).…”
Section: Pregnancy Lossmentioning
confidence: 94%
“…It was found that for every 100 mg/day increment of caffeine consumption, the risk of SAB was increased by 8% (RR = 1.08; 95% CI: 1.04-1.13) and stillbirth by 9% (RR = 1.09; 95% CI: 1.02-1.16). In a meta-analysis of 2 studies by Ng et al [47] it was shown that the risk of recurrent pregnancy loss in the group of women with higher caffeine consumption (> 99 mg/day) compared to the group with lower caffeine consumption (< 99 mg/day) was higher, but not statistically significant (OR = 1.35; 95% CI: 0.83-2. 19).…”
Section: Pregnancy Lossmentioning
confidence: 94%
“…Etiological factors of RPL include advanced maternal age, immunological problems, endocrine dysfunction, and anomalies of maternal anatomy, chromosomes, and placenta [ 5 , 6 , 7 ]. Moreover, environmental factors such as infection, smoking, alcohol, psychological trauma, and stress may contribute to RPL [ 8 , 9 , 10 ]. However, the cause of RPL is unclear in 30–40% of cases, and recent studies suggest that genetic factors play an important role in the pathogenesis of idiopathic RPL [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some women may be able to achieve pregnancy, they may not be able to maintain that pregnancy throughout gestation and deliver a live-born infant. SAB has an occurrence rate of approximately 10%, while that of recurrent SAB is approximately 5% (1). There are many factors that affect early pregnancy abortion.…”
Section: Introductionmentioning
confidence: 99%